Residential perspectives: the value of Floodplain‐ buyout open space - Zavar, Elyse (Geographical Review, 2015)
This mixed-methods case study identifies how floodplain property acquisitiona buyoutimpacts an urban environment at the neighborhood scale while considering the role of individual residents in formal and informal land-use decision making. In floodplain buyouts, the reopening of urban space is enabled by federal structural drivers, primarily Federal Emergency Management Agency (FEMA), but it is repurposed as a cultural landscape constructed and produced by individuals. This research explores how residents perceive and ascribe values to the buyout landscape in Lexington, Kentucky. Enabled by federal funds, but left largely to their own devices, residents in Lexington adopted uses, ascribed values, and produced their own land-use norms in each buyout neighborhood.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-849-610-654-018 tex.type: [object Object]
Keywords: dept.egm; floodplain; land management; land value; peer-reviewed; property acquisition